eInnovation: The importance of context (Revista Galega de Economía)
Today, innovation is ‘in the hands of the masses’; because it is driven by a combination of advances in technology, global communication, connectivity, consumerism, sustainability, societies and social conscience. To survive, in such economies, enterprises and other organisational entities need to consistently and continuously innovate. Innovation, however, is constructed from a set of tendencies and not a final condition in itself. These tendencies are geographically, organisationally and societally different and uneven. Different contextual settings lead to different innovations. This new era of innovation extends the impact of technologies and digitisation in dynamic unanticipated ways leading to paradigm shifts that force us, collectively and individually, to ensure benefits for the many, rather than the few. Therefore, innovation must be established as a ‘way of thinking’ a ‘way of doing’ no matter the context. The key message to be extracted from this paper is that innovation is very much dependent on context. It is dependent of the context of the firm, government policy, absorptive capacity of citizens and on the processes in place to develop human capital.